Evidence to Support Peer Tutoring Programs at the Undergraduate Level. Issue 1 (2nd January 2015) - Colver, Mitchell; Fry, Trevor
Abstract : The present study examined undergraduate peer tutoring in three phases. Phase I qualitatively surveyed students' perceptions about the effectiveness of tutoring. Phase II examined the usefulness of promoting regular use of services through a tutoring contract. Phase III utilized an archival, quasi-experimental approach to estimate the effect of peer tutoring on students who repeated an undergraduate course and either received tutoring or did not receive tutoring during their second attempt. Results revealed a significant estimated treatment effect, lending support to a causal relationship between tutoring and final course outcomes. Tutoring was especially beneficial for first-generation college students.